Gut carriage of antimicrobial resistance genes in women exposed to small-scale poultry farms in rural Uganda: A feasibility study - Weil, Ana A.; Debela, Meti D.; Muyanja, Daniel M.; Kakuhikire, Bernard; Baguma, Charles; Bangsberg, David R.; TsaiI, Alexander C.; Lai, Peggy S. (PloS one, 2020)
Background: Antibiotic use for livestock is presumed to be a contributor to the acquisition of antimicrobial resistance (AMR) genes in humans, yet studies do not capture AMR data before and after livestock introduction. Methods We performed a feasibility study by recruiting a subset of women in a delayed-start randomized controlled trial of small-scale chicken farming to examine the prevalence of clinically relevant AMR genes. Stool samples were obtained at baseline and one- year post-randomization from five intervention women who received chickens at the start of the study, six control women who did not receive chickens until the end of the study, and from chickens provided to the control group at the end of the study. Stool was screened for 87 clinically significant AMR genes using a commercially available qPCR array (Qiagen). Results Chickens harbored 23 AMR genes from classes found in humans as well as additional vancomycin and β lactamase resistance genes. AMR patterns between intervention and control women appeared more similar at baseline than one year post randomization (PERMANOVA R2 = 0.081, p = 0.61 at baseline, R2 = 0.186, p = 0.09 at 12 months) Women in the control group who had direct contact with the chickens sampled in the study had greater similarities in AMR gene patterns to chickens than those in the intervention group who did not have direct contact with chickens sampled (p = 0.01). However, at one year there was a trend towards increased similarity in AMR patterns between humans in both groups and the chickens sampled (p = 0.06). Conclusions Studies designed to evaluate human AMR genes in the setting of animal exposure should account for high baseline AMR rates. Concomitant collection of animal, human, and environmental samples over time is recommended to determine the directionality and source of AMR genes.
Keywords: Gut carriage; Antimicrobial; feasibility study